KEUNIKAN MEREK, KEPRIBADIAN MEREK, PERSEPSI HARGA TERHADAP LOYALITAS DAN PREFERENSI MEREK PADA NIAT PEMBELIAN BERULANG - Swastika, Berliana; Hartono, Arif (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The telecommunications industry, especially mobile phones or smartphones, is an industry that is growing very rapidly. Currently, smartphones are also used as a lifestyle fulfillment, exchange information, and socialize. This study aims to examine the effect of brand uniqueness, brand personality, price perception, brand loyalty, and brand preference have a positive and significant effect on repeat purchase intentions on smartphone products. The population of this study are students who use smartphones in their daily activities. The sampling technique used is the convenience sampling method, with a sample of 134 respondents. This study uses a quantitative approach. The data used is primary data collected through questionnaires and distributed online. The data analysis method used descriptive analysis which was processed using SPSS software and SEM analysis which was processed using SmartPLS software. The results of this study indicate that brand uniqueness, brand personality, price perception, brand loyalty, and brand preference have a positive and significant effect on repeat purchase intentions